Determination of feeding performance of mustard aphid, Lipaphis erysimi (Kalt.) on different mustard varieties at water stress condition - Bari, G M Morshedul; Bari, G M Morshedul; Ahmad, Masum; Rahman, Md Rashedur (Fundamental and Applied Agriculture, 2018)
The more feeding of plant sap by aphid, the more secretion of honeydew. Determination of the amount of honeydew secreted by aphids in a specific crop variety is one of the best ways to assess the susceptibility of aphid infestation to the variety. An experiment was conducted in glass house and controlled growth room of Bangladesh Institute of Nuclear Agriculture (BINA) at 25 ◦C, RH 65–70% and 12:12 hrs daylight on 15 November 2016. Six mustard varieties were evaluated to determine the intensity of honeydew excretion by aphids for assessing susceptibility of aphids in mustard varieties under different water stress condition likely 100% field capacity (control), 50% field capacity (moderate drought) and 30% field capacity (severe drought). Aphid feeding and honeydew secretion were remarkably negatively affected by water stress. Weight of honeydew secreted by a mustard aphid during 24 hrs was reduced by 13% and 25% when subjected to moderate and extreme drought respectively compared to that at non-stressed control. The weight of honeydew secreted by a mustard aphid in 24 hrs in the varieties of Brassica campestris, B. napus and B. juncea was measured ranging 7.65 to 8.85 mg; 4.81 to 5.15 mg and 8.87 to 9.17 mg, respectively. It may be concluded that feeding performance of aphid and honeydew secretion were more in susceptible varieties and negatively affected by water stress. The varieties of B. napus are more resistant to aphid infestation.